A Cost Effective Alternative To Credit Rating Specifically For Smes In India - Singhal, Gaurav (2008)
Journalist Thomas Friedman once said, “There are two superpowers in the world today. There’s the United States and there is Moody’s bond rating services. The US can destroy by dropping bombs and Moody’s can destroy you by downgrading your bonds. Rating agencies play a key role in the infrastructure of modern financial system. The origins of Credit Rating can be traced to the 1840s, following the financial crisis of 1837, Louis Tappan established the first mercantile credit agency in New York in 1841. The agency rated the ability of merchants to pay their financial obligations. It was subsequently acquired by Robert Dun and its first rating guide was published in 1859. Another similar agency was setup by John Bradsheet in 1849, which published a rating book in 1857. 0These two agencies were merged together to form Dun and Bradsheet, in 1933, which became the owner of Moody’s investor service in 1962.